The bifidogenic effect of Taraxacum officinale root - Trojanová, I; Rada, V; Kokoska, L; Vlková, E (Fitoterapia, 2004)
The infusion of dandelion root (Taraxacum officinale) stimulated in vitro the growth of 14 strains of bifidobacteria. The utilization of oligofructans, glucose, fructose and total saccharides was determined by enzymatic and phenol-sulfuric methods. Dandelion oligofructans were important source of carbon and energy for bifidobacteria tested.
Keywords: Microbial Sensitivity Tests; kultivační média; mikrobiální testy citlivosti; Humans; Plant Roots; Bifidobacterium; kořeny rostlin; lidé; Phytotherapy; Taraxacum; fytoterapie; Culture Media